Pengaruh Word of Mouth Dalam Membentuk Citra Merek dan Pengaruhnya terhadap Minat Beli Produk iPhone : (Studi pada Masyarakat Muslim di Kota Bone) - Wulandari, Septi Ayu; Rasyid R, Abd.; Buhasyim, Muhammad Abdi (Interdisciplinary Journal (IDe), 2024)
The abstract contains a brief description of the research objectives, the location of the study, the approach or method used, data analysis tools, and important results and policy implications. Do not include formulas and references in the abstract. The abstract consists of a single paragraph and should not exceed 200 words, using a single space, Arial font, size This research aims to determine the influence of word of mouth and brand image on interest in purchasing iPhone products in Bone City, to determine the influence of word of mouth on the brand image of iPhone products in Bone City, and to determine the role of brand image as a variable that mediates the influence of word of mouth regarding interest in buying iPhone products in Bone City. This research was carried out in 3 sub-districts located in Bone City, namely Kec. Tanete Riattang, East Tanete Riattang and West Tanete Riattang. The approach to this research uses a quantitative approach. Data were analyzed using path analysis and Sobel test. The results of this research show that word of mouth has a significant positive effect on brand image and interest in purchasing iPhone products in Bone City. Good word of mouth can improve brand image and increase consumer buying interest, with brand image functioning as a mediator that strengthens this relationship. These findings emphasize the importance of positive word of mouth in marketing strategies. Apart from that, the ethical principles of QS. Al-Hujurat verse 12 is also relevant in maintaining the honesty and integrity of marketing communications.